Village Mountain Resort Di Palutungan Kabupaten Kuningan Jawa Barat - Kusuma, Rio Januar Arga, Ir. Indrawati,MT, Ir. Samsudin Raidi, M.Sc (2016)
Kuningan regency has a lot of attractions are quite interesting and the potential to be marketed. Unfortunately quite a lot of tourist in the district of Kuningan which is still not well ordered in accordance with the standards of tourism. Therefore, in the design the resort area to facilitate the activities of tourism. The site selected for the construction of Village Mountain Resort is in Palutungan, Cisantana Village, District Cigugur, Kuningan regency. Site has an area of ± 82,000 m2. According to the regulations, the site is dedicated to the development of the tourism sector. Therefore, it is suitable for the activities Village Mountain Resort. In the Village Mountain Resort are dwelling in the form of a cottage as a means to stay for tourists. In addition, there are also restaurants, parks and mosques as a means of worship.